High event‐free survival rate with minimum‐dose‐anthracycline treatment in childhood acute promyelocytic leukaemia: a nationwide prospective study by the Japanese Paediatric Leukaemia/Lymphoma Study Group. (31st March 2016) - Takahashi, Hiroyuki; Watanabe, Tomoyuki; Kinoshita, Akitoshi; Yuza, Yuki; Moritake, Hiroshi; Terui, Kiminori; Iwamoto, Shotaro; Nakayama, Hideki; Shimada, Akira; Kudo, Kazuko; Taki, Tomohiko; Yabe, Miharu; et al.
Abstract : We evaluated the efficacy of treatment using reduced cumulative doses of anthracyclines in children with acute promyelocytic leukaemia (APL) in the Japanese Paediatric Leukaemia/Lymphoma Study Group AML‐P05 study. All patients received two and three subsequent courses of induction and consolidation chemotherapy respectively, consisting of all‐ trans retinoic acid (ATRA), cytarabine and anthracyclines, followed by maintenance therapy with ATRA. Notably, a single administration of anthracyclines was introduced in the second induction and all consolidation therapies to minimize total doses of anthracycline. The 3‐year event‐free (EFS) and overall survival rates for 43 eligible children were 83·6% [95% confidence interval (CI): 68·6–91·8%] and 90·7% (95% CI: 77·1–96·4%), respectively. Although two patients died of intracranial haemorrhage or infection during induction phases, no cardiac adverse events or treatment‐related deaths were observed during subsequent phases. Patients not displaying M1 marrow after the first induction therapy, or those under 5 years of age at diagnosis, showed inferior outcomes (3‐year EFS rate; 33·3% (95% CI: 19·3–67·6%) and 54·6% (95% CI: 22·9–78·0%), respectively). In conclusion, a single administration of anthracycline during each consolidation phase was sufficient for treating childhood APL. In younger children, however, conventional ATRA and chemotherapy may be insufficient so that alternative therapies should be considered.